Tokenism in Legislation: A Critical Analysis of Public Participation in Legal Reform in Indonesia - Tjarsadiwiryo, Fikriansyah (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2025)
This article examines the phenomenon of tokenism in public participation within the legislative process in Indonesia. Adopting a normative legal approach and the conceptual framework of tokenism, this study analyzes the extent to which public participation in lawmaking tends to function more as a formality than as meaningful involvement. The findings indicate that, despite the existence of a supportive legal framework, the practical implementation of public participation remains largely symbolic. This analysis underscores the urgent need for legislative reform that is more inclusive, deliberative, and accountable, enabling public participation to meaningfully contribute to the quality of legislation in Indonesia.